Observational Study of Foreign Bodies in Ear, Nose and Throat at ENT-HNS OPD AND Emergency Department of Birat Medical College and Teaching Hospital - Giri, Sandarva; Kumar Shah, Rajeev; Pokhrel, Aahana; Agarwal, Rajat; Ahmed Khan , Sajjad; Kirti, Anila (Birat Journal of Health Sciences, 2024)
Introduction: Foreign bodies in the ear, nose and throat is the most common problem encountered in outpatient clinic of Ear, Nose and Throat (ENT) and the emergency departments, and their prompt diagnosis is imperative for preventing life-threatening complications.Objectives: The aim of this study was to evaluate the types of foreign bodies impacted in the ENT and to describe the socio-demographic profiles of the presenting patients. Methodology: In a descriptive cross-sectional study conducted at the ENT outpatient clinic and the emergency department of Birat Medical College and Teaching Hospital, Tankisinuwari, Morang, Nepal, 72 patients presenting with impacted foreign bodies in their ENT regions were evaluated for their socio-demographic characteristics, types of foreign bodies and the treatment modality.Results: Of the total of 72 participants, males were 72.2%; age ranging from 2 years to 64 years with the mean age of 22.6; Indo-Aryans (70.8%), and residents around Biratnagar and nearby were 51.4%. Throat was the most commonly involved anatomical site (61.1%). Of the various impacted foreign bodies, the most common were non-living (organic) (58.3%). Specifically, chicken bones (25.0%) followed by coin (12.5%), fish bone (9.7%), mutton bone and cotton (8.3% each) were the most frequently impacted foreign bodies, most cases of which were removed under general anesthesia (55.6%).Conclusion: Males were more commonly involved than females and adults more than the pediatric age groups. Throat was the most commonly involved region and the most common foreign bodies impacted were non-living (organic) in nature, and most of the cases were operated under general anesthesia.Keywords: Ear, nose and throat; Impacted foreign bodies; socio-demography; management.